Proteases as antimalarial targets: strategies for genetic, chemical, and therapeutic validation. (3rd July 2017) - Deu, Edgar
Abstract : Malaria is a devastating parasitic disease affecting half of the world's population. The rapid emergence of resistance against new antimalarial drugs, including artemisinin‐based therapies, has made the development of drugs with novel mechanisms of action extremely urgent. Proteases are enzymes proven to be well suited for target‐based drug development due to our knowledge of their enzymatic mechanisms and active site structures. More importantly, Plasmodium proteases have been shown to be involved in a variety of pathways that are essential for parasite survival. However, pharmacological rather than target‐based approaches have dominated the field of antimalarial drug development, in part due to the challenge of robustly validating Plasmodium targets at the genetic level. Fortunately, over the last few years there has been significant progress in the development of efficient genetic methods to modify the parasite, including several conditional approaches. This progress is finally allowing us not only to validate essential genes genetically, but also to study their molecular functions. In this review, I present our current understanding of the biological role proteases play in the malaria parasite life cycle. I also discuss how the recent advances in Plasmodium genetics, the improvement of protease‐oriented chemical biology approaches, and the development of malaria‐focused pharmacological assays, can be combined to achieve a robust biological, chemical and therapeutic validation of Plasmodium proteases as viable drug targets. Abstract : Proteases play a variety of biological functions in the malaria parasite. These include core biological processes such as protein homeostasis and traffic, but also parasite‐specific functions (haemoglobin degradation, parasite egress, red blood cell invasion). This review provides an overview about the role of proteases in parasite development and outlines chemical and genetic strategies to validate proteases as therapeutic targets.